Evaluation of hydrophylic montmorillonite nanofluids and xantane gum in saline environment (Research, Society and Development, 2020)
With an estimated increasing oil demand in the coming decades, the need to explore non-applicable areas is intensified, and associated with them, before the high exploration costs, the need to improve available technologies. In this sense, in the last decade, the application of nanoparticles to improve drilling fluids has been intensified. In this scenario, montmorillonite nanoclays and xanthan gums were little explored for the development of nanofluids. In this work, the influence of hydrophilic nanoclay on the rheological parameters of xanthan, sodium and calcium chlorides solutions was verified. For this, first, the clay was characterized by XRD, XRF and TGA. Then, maintaining constant the salt and xanthan concentrations, the influence of the variation in the concentration of nanoclay on the rheology of the solution was evaluated. Then, keeping the components concentrations constant, the influence of temperature was verified and then the hydration time on the rheology of the mixture. Finally, to assess the interaction of the mixture, it was verified the Electrical Conductivity and the Potential Zeta, varying the concentration of the nanoclay and the hydration time. It was concluded that: for certain nanoclay concentrations, there is an improvement in the rheology of xanthan solutions; an addition of nanoclay favors rheology in the mixture of xanthan with increased temperature; hydration time does not affect the rheology of the nanofluid; there is interaction between nanoclay and xanthan.